'Antisocial Behaviour, Unfriendly Relations': Assessing the Contemporary Value of the Categories of Unfriendly Acts and Retorsion in International Law. (3rd September 2021) - McDonald, Neil; McLeod, Anna
Abstract: This article considers the international law categories of unfriendly acts and retorsion in the modern context. To date, these categories articulating the freedoms that States enjoy below the threshold of international wrongfulness have received little attention in academic debate. But we consider both categories are of increasing relevance in the context of modern international conflict (in the broadest sense) and inter-State competition, particularly in relation to the regulation of hostile cyber activity between States. Unfriendly acts denotes State activity which, while lawful as a matter of international law, would nonetheless not be welcomed by the States it targets. Retorsion covers another sub-set of lawful but unfriendly State activity, substantively the same as unfriendly acts but done in response to prior unwelcome acts of other States. Having defined these categories, including by reference to a survey of contemporary State practice and judicial treatment, this article then considers why their utility and relevance to States are increasing. The article ends on the cautionary note that while unfriendly acts and retorsion may be increasingly necessary and desirable to States as international law tools as hostile activity occupies more of the space below forcible acts, they equally need to be properly understood and 'handled with care' by international lawyers, to ensure they are not bestowed with legal characteristics they do not possess, unduly constraining States in the process. The risk of misuse of these categories by States also needs to be kept in mind.